PENGARUH CORPORATE SOCIAL RESPONSIBILITY, UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia pada Tahun 2016-2020): THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY, COMPANY SIZE AND SALES GROWTH ON COMPANY VALUE (Empirical Study on Consumer Goods Industry Sector Companies Listed on the Indonesia Stock Exchange in 2016-2020) - Awaludin, Dipateruna Teruna; Hasanudin, Hasanudin; Achyarsyah, Padri; Wulandari, Rizma (JURNAL REKAYASA INFORMASI, 2024)
ABSTRACT This study aims to analyze whether there is an influence of corporate social responsibility, company size, and sales growth on company value. The population in this study is manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. The sampling technique was purposive sampling and the sample used consisted of 155 companies in the observation period 2016-2020. The type of data in this study is secondary data using data from financial reports. The data analysis technique used is multiple linear regression analysis and the data is processed using the SPSS program version 23.0. The results of this study indicate that corporate social responsibility does not affect company value, and sales growth does not affect company value. While company size has a positive effect on company value. Keyword : Corporate Social Responsibility, Company Size, Sales Growth